Comparison between Hazen-Williams and Darcy-Weisbach equations to calculate head loss through conveyancing treated wastewater in Kerbala city, Iraq - Abdulameer, Layth Saeed; Dzhumagulova, Nazira; Algretawee, Hayder; Zhuravleva, Larisa; Alshammari, Musa Habib (Eastern-European Journal of Enterprise Technologies, 2022)
Reuse of wastewater has been widespread in this era to support the water sustainability process. Therefore, treated wastewater should be conveyed to suitable places and adopted for different uses. This study presents an empirical relationship between the Darcy-Weisbach and Hazen-Williams equations for four types of pipe material (ductile iron, GRP, concrete, and plastic) by using WaterCAD Version 8i. Two hydraulic models were developed to estimate the head loss in pipes by using different diameters: first, using pipe diameters from 800 mm to 1,200 mm for a flow rate of 1.16 m3/s, second, adopting pipe diameter from 1,600 mm to 2,000 mm for a flow rate of 4.63 m3/s. The study results are the head loss values obtained from the Darcy-Weisbach and Hazen-Williams equations, which were used to correlate them using IBM SPSS Statistics. The correlation coefficient between both equations turned out to be 0.991, 0.990, 0.990, and 0.990 for ductile iron, GRP, concrete, and plastic pipe materials. Additionally, the relationship between head loss and pipe diameter is negatively proportioned for both equations. Also, both head loss equation results are the same. The head loss values in the Darcy’s equation were higher for ductile iron and GRP materials, while being lower for concrete and plastic materials for both models. Selecting concrete or plastic pipes to convey treated wastewater is better than other pipe materials. Another conclusion is that the pipe diameter affects the head loss magnitude irrespective of the kind of equation whether Darcy-Weisbach or Hazen-William equation. Finally, this relationship is very useful for designers in converting the head loss values obtained using these equations.